2016
DOI: 10.1103/physrevaccelbeams.19.111002
|View full text |Cite
|
Sign up to set email alerts
|

Radiation damage and thermal shock response of carbon-fiber-reinforced materials to intense high-energy proton beams

Abstract: A comprehensive study on the effects of energetic protons on carbon-fiber composites and compounds under consideration for use as low-Z pion production targets in future high-power accelerators and low-impedance collimating elements for intercepting TeV-level protons at the Large Hadron Collider has been undertaken addressing two key areas, namely, thermal shock absorption and resistance to irradiation damage. Carbon-fiber composites of various fiber weaves have been widely used in aerospace industries due to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
10
0
2
Order By: Relevance
“…Several studies [20][21][22][23][24] focusing on energetic proton irradiation effects on the physiomechanical properties and the changes in the microstructure have been conducted in recent years. This is prompted by the fact that graphite, in its various grades including POCO ZXF-5Q of the NuMI target, has been used in several neutrino experiment initiatives (NuMI/MINOS, T2K, and CNGS) as a low-Z material producing a desired pion spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies [20][21][22][23][24] focusing on energetic proton irradiation effects on the physiomechanical properties and the changes in the microstructure have been conducted in recent years. This is prompted by the fact that graphite, in its various grades including POCO ZXF-5Q of the NuMI target, has been used in several neutrino experiment initiatives (NuMI/MINOS, T2K, and CNGS) as a low-Z material producing a desired pion spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Section II summarizes relevant results of past studies [21][22][23][24] on the POCO ZXF-5Q and other isotropic graphites from high neutron and proton fluences. We shall use these data as the basis for interpreting the changes induced by the 120 GeV proton beams.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, beryllium in various grades has been studied [1][2][3][4] under the effects of neutrons for use in nuclear fission or fusion reactors and proton effects [5][6][7][8] on beryllium and AlBeMet (a material metal matrix made of 62% beryllium and 38% aluminum by weight) for accelerator applications (targets and beam windows). Various grades of graphite have been explored over the decades for use as a nuclear reactor moderator material [9][10][11][12][13][14] and target in multi-MW proton accelerators [15,16]. Proton irradiation studies on graphite and carbon composites [15,16] revealed a crucial fluence threshold (∼5 × 10 20 p=cm 2 at low irradiation temperature 80°C-200°C) that could affect the ability of the graphite to maintain its structural integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Various grades of graphite have been explored over the decades for use as a nuclear reactor moderator material [9][10][11][12][13][14] and target in multi-MW proton accelerators [15,16]. Proton irradiation studies on graphite and carbon composites [15,16] revealed a crucial fluence threshold (∼5 × 10 20 p=cm 2 at low irradiation temperature 80°C-200°C) that could affect the ability of the graphite to maintain its structural integrity. In addition, proton-induced damage has shown similarities with fast neutron-induced damage in terms of microscopic and macroscopic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation